Triglyceride Glucose (TyG) Index: A surrogate biomarker of insulin resistance - Vineetha K Ramdas Nayak; Praseeda Satheesh; Mohan T Shenoy; Sanjay Kalra (Journal of the Pakistan Medical Association, 2022)
The predictability of triglyceride glucose index (TyG index) as a biomarker for identification of insulin resistance (IR) is being extensively studied in various ethnic populations. TyG index could be a beneficial tool for identification of IR and populations at high risk for developing diabetes in future. However, more studies are required to standardize optimal cut-off values in different ethnicities and populations. The present review describes existing literature, and identifies merits and demerits of TyG index as a surrogate marker for IR. Keywords: Triglyceride Glucose Index, Insulin resistance, Type 2 Diabetes Mellitus.